Diffusion Mechanism of Leading Technology in the New Energy Industry Based on the Bass Model - Wang, Hongying; Sun, Bing (Frontiers in Energy Research, 2021)
With the increasing global warming problem, new energy industry has become the mainstay of achieving sustainable development of human society. The effective diffusion of leading technologies is the source of social benefits for enterprise core technologies, and it is also a necessary factor for industrial transformation and optimization. In the international context of energy conservation and emission reduction, a systematic and in-depth study of the diffusion mechanism of leading technologies in new energy industry have important theoretical and practical significance for promoting the diffusion of leading technologies in new energy industry. Based on the introduction of Bass model and its extension model, the paper constructs the diffusion model of new energy industry's leading technology and analyzes the diffusion mechanism. The mechanism shows that in the case of imperfect market environment and policy environment, the diffusion of new energy industry's leading technology is mainly influenced by the "expected utility" of innovators and "actual utility" of imitators. The influence is verified by simulation analysis. Based on the diffusion mechanism, we also give some suggestions to promote the diffusion mechanism of new energy industry leading technology, aiming to provide reference for the government, industry associations and enterprises in making relevant decisions.